2015
DOI: 10.1080/19443994.2014.934112
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of petrochemical wastewater by employing membrane bioreactors: a case study of effluents discharged to a sensitive water recipient

Abstract: This work was conducted at the largest petrochemical membrane bioreactor (MBR) plant in the world. The effectiveness of MBR technology to treat petrochemical effluents was studied. The treated effluent is discharged in a very sensitive water body and needs to satisfy strict limits. To optimize MBR operation a pilot-scale MBR was set-up that received the same petrochemical effluents as the full scale. In the pre-denitrification configurations, ammonification was not effective. Variable removal of heavy metals/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As shown in Table 3, Malamis et al, (2015) showed that membrane bioreactor (MBR) removed heavy metals from petrochemical wastewater in different removal percentages, which range from 40% to 70%, and only iron removal was the maximum removal in this process, being higher than 70%. Moslehyani et al, (2015) indicated that the best nanocomposite membrane was nanocomposite membrane with the multi-walled carbon nanotube (MWCNT) incorporated in Polyvinylidene fluoride (PVDF) matrix for the filtration purposes because it removed all pollutants from refinery wastewater and it was the excellent anti-fouling property.…”
Section: Membranementioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Table 3, Malamis et al, (2015) showed that membrane bioreactor (MBR) removed heavy metals from petrochemical wastewater in different removal percentages, which range from 40% to 70%, and only iron removal was the maximum removal in this process, being higher than 70%. Moslehyani et al, (2015) indicated that the best nanocomposite membrane was nanocomposite membrane with the multi-walled carbon nanotube (MWCNT) incorporated in Polyvinylidene fluoride (PVDF) matrix for the filtration purposes because it removed all pollutants from refinery wastewater and it was the excellent anti-fouling property.…”
Section: Membranementioning
confidence: 98%
“…Membranes could be generally classified into biological membranes (Malamis et al, 2015;Razavi and Miri, 2015) and synthetic membranes. Membrane technologies such as electrodialysis and ultra-filtration are being applied increasingly.…”
Section: Membranementioning
confidence: 99%
“…Membranes could be generally classified into biological membranes (Malamis et al, 2015;Razavi and Miri, 2015) and synthetic membranes. Membrane separation was found useful in treating organic matter and more acceptable and economic than other physical treatment techniques (Jyoti et al, 2013;Kulkarni and Goswami, 2014).…”
Section: Membranesmentioning
confidence: 99%